2016
DOI: 10.5664/jcsm.5694
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and Objective Measures of Hypersomnolence Demonstrate Divergent Associations with Depression among Participants in the Wisconsin Sleep Cohort Study

Abstract: A commentary on this article appears in this issue on page 467.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 50 publications
(50 reference statements)
2
26
1
Order By: Relevance
“…In the clinical protocol, participants were allowed to sleep for 15 min after sleep onset during naps to assess for sleep onset rapid eye movement (REM) periods. Because prior cross-sectional analyses have demonstrated nearly identical associations between mean SOL on MSLT and depressive symptoms using either protocol, as well as previous reports that have shown preceding polysomnography has minimal effects on mean SOL on MSLT, results from both protocols were combined for these analyses (Plante et al, 2016; Wichniak et al, 2002). Mean SOL below 8 minutes averaged across the first four nap opportunities defined objective EDS in these analyses, consistent with current nosology (American Academy of Sleep Medicine, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the clinical protocol, participants were allowed to sleep for 15 min after sleep onset during naps to assess for sleep onset rapid eye movement (REM) periods. Because prior cross-sectional analyses have demonstrated nearly identical associations between mean SOL on MSLT and depressive symptoms using either protocol, as well as previous reports that have shown preceding polysomnography has minimal effects on mean SOL on MSLT, results from both protocols were combined for these analyses (Plante et al, 2016; Wichniak et al, 2002). Mean SOL below 8 minutes averaged across the first four nap opportunities defined objective EDS in these analyses, consistent with current nosology (American Academy of Sleep Medicine, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a universal limitation of all prior studies has been reliance on self-report measures to assess EDS. The absence of objective measures of daytime sleepiness, such as the multiple sleep latency test (MSLT), is particularly important because the relationship between objectively quantified sleep propensity and subjective sleepiness is relatively modest (Punjabi et al, 2003), and prior cross-sectional analyses from our group have demonstrated that objective and subjective hypersomnolence measures have divergent associations with depression (Plante et al, 2016). Thus, this current study utilized data from the Wisconsin Sleep Cohort (WSC) Study to examine longitudinal associations of both subjective and objective hypersomnolence measures with depression using conditional logistic regression analyses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plante et al [19] further reported that odds ratios for depression were higher in patients with high ESS scores, in contrast to findings obtained for MSLT scores, suggesting that subjective scale scores may be affected by events other than sleepiness. Moreover, Leclerc et al [20] reported that pre-intervention ESS scores were significantly lower when measured prior to therapeutic interventions for OSA syndrome than when measured via recall following CPAP therapy.…”
Section: Discussionmentioning
confidence: 43%
“…Suicide attempts are not only a severe health problem, but also contribute substantially to the economic burden (Kadotani et al 2014). Previous studies have further indicated that the severity of depression is associated with symptoms such as insomnia, daytime sleepiness, short sleep duration, and a reduction in productivity at work, even among undiagnosed individuals (Jha et al 2016;Penninx et al 2008;Plante et al 2016;Baglioni et al 2011;Nakada et al 2015). Therefore, in the present study, we aimed to analyze the association among depression, sleep quality, and quality of life using the Japanese version of the SCID-I/NP (First et al 2002), and to compare these findings with those obtained using self-reported scales, in an urban male working population in Japan in order to determine the most effective instrument for screening for depression.…”
Section: Introductionmentioning
confidence: 99%